MEDIA KOMUNIKASI VISUAL ABJAD BISINDO BAGI TUNARUNGU DI KOTA PALEMBANG - muhammad rizky; Heri Iswandi; Mukhsin Patriansah (VisArt: Jurnal Seni Rupa dan Design, 2023)
Abstract : Deafness is a general term that indicates difficulty hearing from mild to severe, classified into deafness and hearing loss. This is because Bisindo comes from the mother tongue, which is the Indonesian language that is used daily, and one movement can represent a word that is also widely known among non-deaf people. This design using Design Thinking method there are several stages such as (Empathize) understand the problem, (Define) identify the problem, (Ideate) find ideas, (Prototype) realize the idea, and (Test) the application of the results. The data collection process is done by, interviews, observations, questionnaires, literature and websites. The data obtained were then processed and analyzed using the method (5W+1H). From the results of this problem resulted in a Visual Communication Design Bisindo Alphabet for the Deaf in Palembang. The purpose of this design is to understand communicating through the Bisindo Alphabet by using conceptual and interesting visual communication elements. and how to communicate with the deaf informative through learning the Alphabet Bisindo. In this design, the media produced such as media Board Education, posters, catalog of works & catalog Alphabet Bisindo, T-shirts, notebooks, hearing aids, X-banners, stickers, Pointing Devices, Tote bags, Instagram feeds, brochures.